Building structures thermal calculation - A. V. Maistrenko (Advanced Engineering Research, 2021)
Introduction. The thermal calculation of a volumetric structure using the finite element method is considered. According to the plans of the Ministry of Energy of the Russian Federation, a powerful wind energy industry will be created in the country in the coming years. In this regard, calculations in the production of building structures of wind power plants are currently becoming a challenge. The production of such fiberglass structures is a complex thermochemical process, including the polymerization of the binder under strictly specified thermal conditions. The work objective is to develop a method for three-dimensional finite element calculation of the non-stationary heating mode of a complexshaped composite structure.Materials and Methods. The determination of the temperature fields of a complex-shaped structure made of inhomogeneous materials causes using numerical methods and, first of all, the finite element method. The finite element modeling of the behavior of composite materials under molding is still incomplete. For its partial solution, the well-known heat conduction equation is adapted for a specific problem based on the first law of thermodynamics. New finite element models describing the thermal fields in the structure during its manufacture are proposed. The accuracy of modeling thermal processes is specified. Numerical simulation of heating is carried out.Results. The solution to the problem was performed in the multifunctional software complex ANSYS with the implementation of the calculation method in the parametric programming language APDL. The temperature fields of the blade elements of wind power plants at the stage of their manufacture were calculated, which made it possible to identify the characteristic features of the production process of these structures and to obtain recommendations for clarifying the process of their gluing.Discussion and Conclusions. The results obtained can be used in thermal calculations of elements of complex layered structures made of composite materials in wind power, mechanical engineering, aircraft, shipbuilding, instrumentation, etc.